Different doses of tenecteplase vs. alteplase for acute ischemic stroke within 4.5 hours of symptom onset: a network meta-analysis of randomized controlled trials - Liang, Huo; Wang, Xue; Quan, Xuemei; Chen, Shijian; Qin, Bin; Liang, Shuolin; Huang, Qiuhui; Zhang, Jian; Liang, Zhijian (Frontiers in Neurology, 2023)
Background The optimal dose of tenecteplase vs. alteplase for acute ischemic stroke (AIS) has yet to be established. Therefore, we included the latest randomized controlled trials (RCT) to assess the efficacy and safety of different doses of tenecteplase vs. alteplase for AIS within 4.5 hours of symptom onset. Methods Literature was searched in PubMed, Cochrane Library, Embase, Web of Science, and clinical trial registries until February 12, 2023. Odds ratios (OR) with 95% credible intervals (CrI) were estimated using Bayesian network meta-analysis (NMA). Treatments were ranked based on efficacy and safety using the surface under the cumulative ranking curve (SUCRA). Results Eleven RCTs with 5,475 patients were included. Tenecteplase 0.25 mg/kg and alteplase 0.9 mg/kg had significantly higher rates of excellent functional outcome (tenecteplase: OR, 1.85; 95% CrI, 1.44–2.37; alteplase: OR, 1.60; 95% CrI, 1.29–1.97) and good functional outcome (tenecteplase: OR, 1.54; 95% CrI, 1.19–1.98; alteplase: OR, 1.40; 95% CrI, 1.14–1.74) than placebo, despite an increased risk of symptomatic intracranial hemorrhage. Furthermore, the NMA (OR, 1.16; 95% CrI, 1.01–1.33) and the pairwise meta-analysis (OR, 1.16; 95% CI, 1.02–1.33; P = 0.03) indicated that tenecteplase 0.25 mg/kg was superior to alteplase 0.9 mg/kg in excellent functional outcome. Alteplase 0.9 mg/kg (OR, 2.54; 95% CrI, 1.45–8.08) significantly increased the risk of any intracranial hemorrhage compared with placebo. SUCRA results demonstrated that tenecteplase 0.25 mg/kg ranked first and tenecteplase 0.4 mg/kg ranked last in efficacy outcomes. Conclusions The NMA indicated that tenecteplase 0.25 mg/kg and alteplase 0.9 mg/kg are safe and significantly improve clinical outcomes in patients with AIS within 4.5 h of symptom onset. Furthermore, tenecteplase 0.25 mg/kg provides more benefit and has the potential to replace alteplase 0.9 mg/kg in AIS treatment. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/index.php, identifier: CRD42022343948.